2021
DOI: 10.3389/fgene.2021.669598
|View full text |Cite
|
Sign up to set email alerts
|

circARL15 Plays a Critical Role in Intervertebral Disc Degeneration by Modulating miR-431-5p/DISC1

Abstract: BackgroundIntervertebral disk degeneration (IDD) is a serious public health problem associated with genetic and environmental factors. However, the pathogenic factors involved and the pathological mechanism of this disease still remain enigmatic.MethodsThe associated microarray was downloaded and further analyzed using statistical software R. The competing endogenous RNA (ceRNA) co-expression network was constructed to measure the meaningful correlated expression of differentially expressed genes. We further m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…The binding between circRNAs and miRNAs regulates cell proliferation, mitophagy, and apoptosis in IDD [ 10 ]. Of note, miR-431-5p has been documented to be upregulated in IDD and circARL15 acts as a ceRNA to reduce miR-431-5p expression, thus inhibiting NPC apoptosis but inducing NPC proliferation to alleviate IDD [ 35 ], providing validation of our finding.…”
Section: Discussionsupporting
confidence: 78%
“…The binding between circRNAs and miRNAs regulates cell proliferation, mitophagy, and apoptosis in IDD [ 10 ]. Of note, miR-431-5p has been documented to be upregulated in IDD and circARL15 acts as a ceRNA to reduce miR-431-5p expression, thus inhibiting NPC apoptosis but inducing NPC proliferation to alleviate IDD [ 35 ], providing validation of our finding.…”
Section: Discussionsupporting
confidence: 78%
“…Hydrogen peroxide can activate the senescence signal transduction pathway and induce cell cycle stagnation in G0/ G1 phase of nucleus pulposus cells. These studies indicate that oxidative stress is an important inducement of intervertebral disc degeneration (Yudoh et al, 2005;Wang et al, 2021a).…”
Section: Introductionmentioning
confidence: 79%
“…Zhang et al [ 36 ] also demonstrated that circSNHG5 inhibited cartilage endplate degradation through sponging mir-495-3p to derepress CITED2. Wang et al [ 37 ] reported that circARL15 modulated IDD progression via regulating the miR-431-5p/DISC1 axis. Zhang et al [ 38 ] demonstrated that circ_ITCH induced ECM degradation through regulating Wnt/β-catenin signaling in IDD.…”
Section: Discussionmentioning
confidence: 99%